MATHEMATICAL MODELING OF HEATING RATE PRODUCT AT HIGH HEAT TREATMENT - M. M. Akhmedova; M. E. Akhmedov; A. F. Demirova; V. V. Pinyaskin (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
Methods of computing and mathematical modeling are all widely used in the study of various heat exchange processes that provide the ability to study the dynamics of the processes, as well as to conduct a reasonable search for the optimal technological parameters of heat treatment.This work is devoted to the identification of correlations among the factors that have the greatest effect on the rate of heating of the product at hightemperature heat sterilization in a stream of hot air, which are chosen as the temperature difference (between the most and least warming up points) and speed cans during heat sterilization.As a result of the experimental data warming of the central and peripheral layers compote of apples in a 3 liter pot at high-temperature heat treatment in a stream of hot air obtained by the regression equation in the form of a seconddegree polynomial, taking into account the effects of pair interaction of these parameters.